Structure analysis of the novel microporous aluminophosphate IST-1 using synchrotron powder diffraction data and HETCOR MAS NMR - Jordá, J. L. (2013)
A combination of advanced powder diffraction and NMR techniques have allowed the structure of the novel microporous aluminophosphate IST-1 (|(CH3NH2)4(CH3NHþ 3 )4(OH )4|½Al12P12O48 ) to be elucidated. The framework structure was determined in the non-centrosymmetric space group Pca21 (a ¼ 9:61523ð1Þ AA, b ¼ 8:67024ð1Þ AA, c ¼ 16:21957ð2Þ AA) from high-resolution synchrotron powder diffraction data using the program FOCUS. Extra framework species were then located on difference electron density maps. A hydroxyl group was found to bridge between two of the framework Al atoms, and one methylamine species, presumably protonated, could be located in the channels where it H-bonds to three framework oxygens. The most unusual feature of the structure is the second methylamine molecule, which bonds directly to a framework Al atom. The structure is entirely consistent with 31P and 27Al MAS NMR studies, which showed there to be three P (all 4-coordinate) and three Al (one 4-, one 5- and one 6-coordinate) sites, and with 13C MAS NMR, which showed there to be two different types of methylamine species in equal amounts. Assignment of the 31P, 27Al and 13C MAS NMR signals could be deduced from the crystallographic data,31P-27Al HETCOR spectra and ab initio calculations.